2006
DOI: 10.1063/1.2178298
|View full text |Cite
|
Sign up to set email alerts
|

Probing anisotropic interaction potentials of unsaturated hydrocarbons with He*(2S3) metastable atom: Attractive-site preference of σ-direction in C2H2 and π-direction in C2H4

Abstract: State-resolved collision energy dependence of Penning ionization cross sections of acetylene (C2H2) and ethylene (C2H4) with He*(2 3S) metastable atoms was observed in a wide collision energy range from 20 to 350 meV. A recently developed discharge nozzle source with a liquid N2 circulator was employed for the measurements in the low-energy range from 20 to 80 meV. Based on classical trajectory calculations for the energy dependence of the partial ionization cross sections, anisotropic potential energy surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…As described previously, 30 the OE method is able to describe effectively anisotropic potentials by expanded terms using overlap integrals between target MOs φ i and an atomic orbital χ. The expansion coefficients C i in eq 5 and the exponent ζ in eq 6 are parameters to be optimized in the potential corrections; however, in our previous studies [30][31][32][33] the optimized values of ζ in eq 6 have been found to be very close to the exponent of the 2s orbital of He* atom, which is 0.575 bohr -1 determined by Slater's rule. According to this fact, the parameter of ζ was fixed at the above value.…”
Section: Calculationsmentioning
confidence: 79%
See 3 more Smart Citations
“…As described previously, 30 the OE method is able to describe effectively anisotropic potentials by expanded terms using overlap integrals between target MOs φ i and an atomic orbital χ. The expansion coefficients C i in eq 5 and the exponent ζ in eq 6 are parameters to be optimized in the potential corrections; however, in our previous studies [30][31][32][33] the optimized values of ζ in eq 6 have been found to be very close to the exponent of the 2s orbital of He* atom, which is 0.575 bohr -1 determined by Slater's rule. According to this fact, the parameter of ζ was fixed at the above value.…”
Section: Calculationsmentioning
confidence: 79%
“…The coefficients C i for the unoccupied MOs (C 5 -C 7 ) are found to be positive, which are consistent with the previous studies. [30][31][32][33] The relative ratio between the optimized K (i) parameters associated with the ionization width for producing respective ionic states Γ (i) in eq 7 is found to be K (X) :K (A) :K (B) :K (C) ) 1.0: 2.2:7.1:15.8. The increasing trend for K (i) with respect to the ionization potentials for the respective ionic states has been discussed in the previous studies.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The basic novelty consists on the following two main points: (i) The radial dependence of the real part of the potential [V t in the Equation (1)], both in the entrance and exit channels, is represented by an Improved Lennard Jones Potential model (ILJ) defined by few parameters related to basic physical properties of the interacting particles (Pirani et al, 2008). Its reliability, tested on high resolution scattering and spectroscopic experiments as well as by ab initio calculations, has been found to be comparable and even better with respect to that of multiparameter functions, widely used in the past, as the TT model (Falcinelli et al, 2017); (ii) The description of the anisotropy in both channels in terms of the same components related to the selective dependence of CT on the half-filled P orbital alignment within the intermediate collision complex; (iii) The internally consistent representation of both real V t and imaginary Γ parts of the optical potential [see Equation (1)] which, for the first time, has been considered not independent (as it has been done until now) but interdependent being related to the selectivity of CT. Other relevant works in the stereodynamical investigation of auto-ionization processes have been carried out by Ohno and coworkers on the He * -molecule systems where the He * is an isotropic reagent and the dependence on the features of the involved molecular orbitals has been characterized (Ohno, 2004; Yamazaki et al, 2005, 2007; Horio et al, 2006; Khishimoto and Ohno, 2007). Important contributions have been also provided by the Kasai group on the dependence of reactions on the orientation of symmetric top molecules investigated in detail considering Ar * as an isotropic collisional partner (Yamato et al, 2000; Brunetti et al, 2001; Ohoyama et al, 2001).…”
Section: Introductionmentioning
confidence: 99%